ANALISIS PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM SHOPEE TERHADAP BRAND LOYALTY DENGAN CUSTOMER ENGAGEMENT SEBAGAI VARIABEL INTERVENING (Studi pada Pengguna Shopee Mahasiswa Aktif Universitas Diponegoro Angkatan 2018-2021) - Josephine Rachelia Meruvishnu; Budi Sudaryanto (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of social media marketing and customer engagement on brand loyalty at Shopee Indonesia. The population used in this study are active students of Diponegoro University class 2018 to 2021 who are shopee users and Instagram users who follow shopee Indonesia's account, namely @shopee_id. The number of samples used in this study were 120 respondents. The method of data collection is done through a questionnaire. This research uses Structural Equation Modeling (SEM) analysis technique with AMOS 23.0 analysis tool. The results of this study indicate that the social media marketing variabel has a positive and significant effect on customer engagement, the customer engagement variabel has a positive and significant effect on brand loyalty and the social media marketing variabel has a positive and significant impact on brand loyalty. The results of this study indicate social media marketing and customer engagement, have a positive and significant effect on brand loyalty